1987
DOI: 10.1002/jcp.1041300320
|View full text |Cite
|
Sign up to set email alerts
|

Ionic responses and growth stimulation in rat astroglial cells: Differential mechanisms of gangliosides and serum

Abstract: Rat astroglial cells respond to fetal calf serum (FCS) and gangliosides, including GM1, by undergoing proliferation. Here, we show that addition of FCS but not GM1 causes an increase in Na+, K+-pump activity, as measured by ouabain-sensitive 86Rb+ influx. The increase of Na+, K+-pump activity by FCS was due to increased Na+ influx (measured with 22Na+). This increased Na+ influx was sensitive to amiloride, an inhibitor of Na+/H+ exchange. Amiloride also blocked the FCS-stimulated incorporation of [3H]thymidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Soluble factors found in CM from cerebellar astrocytes decrease astrocyte proliferation (Aloisi et al, 1987), while an EGF receptor immunoreactive mitogen inhibitor has been reported in brain homogenate and astroglial CM (Nieto and Broderick, 1989). The presence of such an inhibitor may be undetectable in the current studies since 10% FBS is a strong mitogen to astrocytes (Skaper and Varon, 1987). Astrostatine, a soluble factor secreted by neurons (Rogister et al, 1990), has also been suggested as an inhibitor of astrocyte proliferation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Soluble factors found in CM from cerebellar astrocytes decrease astrocyte proliferation (Aloisi et al, 1987), while an EGF receptor immunoreactive mitogen inhibitor has been reported in brain homogenate and astroglial CM (Nieto and Broderick, 1989). The presence of such an inhibitor may be undetectable in the current studies since 10% FBS is a strong mitogen to astrocytes (Skaper and Varon, 1987). Astrostatine, a soluble factor secreted by neurons (Rogister et al, 1990), has also been suggested as an inhibitor of astrocyte proliferation.…”
Section: Discussionmentioning
confidence: 96%
“…Mitogens and growth factors required for the continuous proliferation of astrocytes may drop below threshold levels during maturation, and as a consequence proliferating cells exit the cell cycle. In vitro studies suggest that among the major mitogens for astrocytes are epidermal growth factor (EGF), basic fibroblast growth factor (bFGF), and platelet-derived growth factor (PDGF; Besnard et al, 1987;Hunter et al, 1993;Skaper and Varon, 1987). These ligands drive robust proliferation of cultured astrocytes and are present in the developing and adult CNS.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, bFGF may be paradigmatic. Basic FGF is a well-known stimulator of astrocyte and oligodendrocyte proliferation [196,197]. The mRNA level of bFGF has been shown to be reduced in the dorsolateral prefrontal cortex of patients with major depression [92,198].…”
mentioning
confidence: 99%
“…Radiolabeling of trichloroacetic acid-insoluble material was determined as described previously [37]. The final pellet was resuspended in RPMI 1640 plus 10 per cent FCS and diluted to a concentration of 5000 cells/ml.…”
Section: Cell Growth In Vitromentioning
confidence: 99%